Steady-State and Transient Benchmarks of GOTHIC to the Molten Salt Reactor Experiment. (2nd January 2022) - Harvill, R. C.; Lane, J. W.; Link, J. M.; Claybrook, S. W.; George, T. L.; Kindred, T.
Abstract: The Molten Salt Reactor Experiment (MSRE), which operated at Oak Ridge National Laboratory from 1965 to 1969, was an experimental reactor that used UF4 fuel dissolved in molten fluoride salt. Criticality was achieved when the fuel salt mixture passed through the graphite-moderated core region. Therefore, because the fuel and fission products flowed through the system, delayed neutron precursors were not confined to the core, and decay heat was released outside the core, which is a unique challenge relative to more traditional reactor designs with solid fuel. Therefore, research and demonstration reactors such as MSRE have become a valuable source of information for benchmarking modeling and simulation tools for advanced reactor designs. One such tool being considered is GOTHIC, which is a coarse-grid computational fluid dynamics multiphysics software package. GOTHIC includes attributes and physical phenomena needed for modeling these advanced, non–light water reactor designs. For example, GOTHIC includes fluid property tables for various molten salts; a tracer-tracking module for modeling fission products and the radioactive decay and heat release by delayed neutron precursors locally in the fluid outside the core; and other necessary capabilities for modeling molten salt reactor (MSR) designs, including the ability to model dissolved gases. GOTHIC is used to benchmark steady-state and transient conditions from the MSRE. Zero-power physics testing included fuel salt pump start-up and coast-down transients with a control rod automatically moving to maintain criticality. The control rod motion calculated by GOTHIC is a reasonable match to measured data from these transients. Further, low-power testing included a natural convection transient with no control rod motion such that reactor power was responding to heat load demand from the radiator. The reactor power and fuel salt and coolant salt temperatures calculated by GOTHIC exhibit good agreement with measured data. These results confirm GOTHIC capabilities for modeling MSR designs with circulating fuel.